2017
DOI: 10.1002/ejsp.2316
|View full text |Cite
|
Sign up to set email alerts
|

University socialization and the acceptance of anti‐egalitarian ideology: The underlying role of extrinsic life goals

Abstract: Past research suggests that students in social science often become more egalitarian while students in business and economics show a trend in the opposite direction. Using a cross-sectional study in which we compared first and third year students from different academic environments, we wanted to explore these issues and to test whether life goals may account for potential ideological differences among them. Psychology and economics students at first and third year of their respective academic group completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The finding that egalitarianism plays a role in the association between IA and PWB, and that this trend is present among specific populations, may be of particular interest to universities and college students. Similar to past research, the current studies (Curtin et al, 2015;Greenwood, 2008) identified that young adults, college students, and activists were more likely to have a positive associa tion between IA and PWB, likely due to their higher levels of CCEg (Muheljic & Drace, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…The finding that egalitarianism plays a role in the association between IA and PWB, and that this trend is present among specific populations, may be of particular interest to universities and college students. Similar to past research, the current studies (Curtin et al, 2015;Greenwood, 2008) identified that young adults, college students, and activists were more likely to have a positive associa tion between IA and PWB, likely due to their higher levels of CCEg (Muheljic & Drace, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, social dominance theory posits that the norms of HE occupations can socialize more antiegalitarian beliefs among its members over time. Indeed, prior research shows that antiegalitarian beliefs tend to be higher for those in HE majors (law) than for those in HA majors (psychology) and that these differences are mediated by perceived social norms (Dambrun et al, 2002; Muheljic & Drace, 2018). Further work by Dambrun et al (2009) comparing 1st- and 3rd-year undergraduates showed that exposure to HA academic majors lowered participants’ SDO by decreasing their belief in genetic determinism.…”
Section: Social Dominance Theorymentioning
confidence: 99%
“…This literature assesses the degree to which social dominance orientation (SDO; Pratto, Sidanius, Stallworth, & Malle, 1994)—a measure of one’s preference for hierarchical arrangements in society—predicts people’s membership in occupations that foster (i.e., hierarchy-enhancing [HE]) or mitigate (i.e., hierarchy-attenuating [HA]) intergroup hierarchies. Whereas some studies suggest that people seek out, and are selected into, occupations that match their (dis)inclination for intergroup inequality (Pratto & Espinoza, 2001; Pratto, Stallworth, Sidanius, & Siers, 1997; Sidanius, van Laar, Levin, & Sinclair, 2003), others indicate that the occupational environment may be more critical in shaping the attitudes of its members (Dambrun, Kamiejski, Haddadi, & Duarte, 2009; Muheljic & Drace, 2018; Nicol, Charbonneau, & Boies, 2007).…”
mentioning
confidence: 99%
“…In contrast, Hadjar and Niedermoser (2019) studied the life goals of Swiss high school students and found no effect of the educational history of the parents on the future direction and objectives of the students. It is possible that an increased educational level of the father makes a positive contribution to the development of internal goals of the children through increased awareness of the individual and increased self‐realization as regards internal objectives, such as working in the preferred occupation, having positive objectives, and achieving personal satisfaction (Korkmaz et al, 2015; Muheljic & Drace, 2018). We found students whose parents had not finished primary school to have a lower tendency towards external goals (Table 2).…”
Section: Discussionmentioning
confidence: 99%